ANALYSIS OF PROBLEM SOLVING ABILITY OF CLASS X STUDENTS REVIEWED FROM LEARNING STYLE: ANALISIS KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA SISWA KELAS X DITINJAU DARI GAYA BELAJAR - Andi Mattoliang, Lisnasari; Nursalam; A. Sriyanti; Suharti, Suharti; Ta’a, Raoda Isti (MaPan : Jurnal Matematika dan Pembelajaran, 2024)
It is important to know students’ mathematical problem solving abilities based on their learning styles to identify the most appropriate teaching method to maximize each student's learning potential. This research aims to analyze the mathematical problem solving abilities of class X IIS 1 MA Guppi Ralla students by considering three learning styles, namely visual, auditory, and kinesthetic. The approach used is a qualitative approach. The research subjects consisted of three students, representing various learning styles. Data was collected through learning style questionnaires, problem solving ability tests, and interviews. The data results were analyzed using data reduction, data display, and conclusion drawing. The results of this research indicate that the mathematical problem solving abilities of class X students at MA Guppi Ralla can be influenced by their learning style. Based on the analysis of problem solving abilities in three subjects representing visual, auditory, and kinesthetic learning styles, it can be concluded that students with a visual learning style have good mathematical problem solving abilities, especially in understanding problems, making plans, implementing plans, and looking back. Students with an auditory learning style also have good abilities in solving mathematical problems, although there is some difficulty understanding the problem carefully. Meanwhile, students with a kinesthetic learning style are also capable of solving mathematical problems, but they tend to be less careful in defining problems. Further research could explore how various teaching methods tailored to students' learning styles influence the improvement of their problem solving ability.